Efektivitas Pelaksanaan Monitoring dan Evaluasi Berbasis Aplikasi (E-Monev) pada Dinas Perumahan dan Permukiman (Perkim) Kabupaten Pohuwato - Aprilani Parengring; Salma Abdullah Kiu (Universitas Islam Darul Ulum Lamongan, 2025)
The study concludes that the implementation of performance monitoring and evaluation at the Pohuwato Regency Housing and Settlement Agency (Dinas PERKIM), particularly concerning the Regional Work Plan (Renja OPD) conducted quarterly, remains ineffective. This ineffectiveness stems from the inadequate fulfillment of established effectiveness criteria, including clear objectives, human resources, adequate infrastructure support, and adherence to a coherent value system. Only the organizational structure indicator was found to be functioning optimally. Key impediments identified include the absence of a dedicated operator for the e-Monev application, a lack of technological proficiency among human resources, habitual delays in data submission, and inherent imperfections within the e-Monev application itself. In response to these findings, the Development Division of the Pohuwato Regency Regional Secretariat (SETDA) has initiated a re-planning effort for the e-Monev application to enhance user comprehension. This initiative also encompasses providing further technical guidance (Bimtek) to all Regional Work Units (OPD) within Pohuwato Regency regarding the e-Monev application, allocating dedicated operators to manage monitoring and evaluation activities via the e-Monev platform, and meticulously planning human resource allocation in terms of both quantity and quality. Therefore, it is recommended that Dinas PERKIM Pohuwato Regency, in its execution of e-Monev-based monitoring and evaluation, consistently prioritize the quality and quantity of its existing human resources. Should deficiencies be identified, the agency ought to implement sound human resource management practices. This includes strategic human resource planning to meet organizational needs, and providing comprehensive development and training initiatives to enhance the capabilities, skills, and extensive knowledge of personnel, particularly in technology and the execution of e-Monev-based monitoring and evaluation.